2019
DOI: 10.1039/c9cp02648g
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic and solar cell applications of Janus monolayers and their van der Waals heterostructures

Abstract: Janus monolayers and their van der Waals heterostuctures are investigated by hybrid density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 52 publications
7
85
0
Order By: Relevance
“…41,43,46 A deep understanding of the intrinsic physical mechanism of Janus chromium trihalides and practical methods to control their spin states are highly required. 48,49 Moreover, strain 33,50 and stacking order 19,33,[48][49][50][51][52] are widely used methods to modulate the tunneling magneto-resistances, 29,53 magneto-optical effects, 54 light scattering 31 and topological properties of materials. 15,55,56 In this article, using first-principles methods with vdW interaction corrections, [57][58][59] we investigate the geometric, magnetic, and electronic properties and stability of ML Janus Cr 2 Cl 3 I 3 using hybrid functional-HSE06.…”
Section: Introductionmentioning
confidence: 99%
“…41,43,46 A deep understanding of the intrinsic physical mechanism of Janus chromium trihalides and practical methods to control their spin states are highly required. 48,49 Moreover, strain 33,50 and stacking order 19,33,[48][49][50][51][52] are widely used methods to modulate the tunneling magneto-resistances, 29,53 magneto-optical effects, 54 light scattering 31 and topological properties of materials. 15,55,56 In this article, using first-principles methods with vdW interaction corrections, [57][58][59] we investigate the geometric, magnetic, and electronic properties and stability of ML Janus Cr 2 Cl 3 I 3 using hybrid functional-HSE06.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] In photovoltaics, the efficiency of a device is linked to effective carrier masses, which relate to the charger extraction and recombination dynamics and control the open‐circuit voltage. [ 33 ] The carrier mobility, as one of the key properties of photovoltaics, depends on both the momentum relaxation time and effective mass, where the momentum relaxation time is inversely linked to the effective mass in lattice scattering. [ 34 ] It is shown that a large effective mass results in a decreased charge carrier mobility, which therefore lowers the efficiency of light conversion in photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many vertical stacked vdW heterostructures have been theoretically predicted, even though experiments, and used to manufacture nanodevices with desired characteristics and unique functions. [28][29][30][31][32][33] Most recently, GeC-MSSe (M ¼ Mo, W), g-GaN-transition metal dichalcogenides, 34 blueP-SiC-BSe heterostructures, 35 Janus-Janus heterostructures, 36 TMDCs-TMDCs heterostructures, 37 SiC-TMDCs heterostructures 38 and SnSe 2 -MoS 2 (ref. 39) heterostructures have been predicted theoretically and fabricated experimentally.…”
Section: Introductionmentioning
confidence: 99%